Solar powered space vector pulse width modulation based induction motor drive for industry applications - Muhammad Sohaib Choudhary; Muhammad Saqlain Saqi; Muhammad Rameez Javed; Hasan Erteza Gelani; Muhammad Akram; Muhammad Kashif Amjad; Sana Khan (Institute of Advanced Engineering and Science, 2022)
The new millennium has witnessed a rapid growth in the development of solar-powered electric systems as well as variable frequency drives (VFDs). Predominantly, pulse width modulation (PWM) based adjustable frequency drives are being employed in the industry for providing superior performance. The space vector pulse width modulation (SVPWM) has gained importance due to its improved harmonic profile. In the current effort, SVPWM based VFD for an induction motor is devised equipped with a push-pull converter for optimal performance. A feedback system is incorporated for motor controls. The SVPWM is implemented using FPGA based my-RIO controller because of its effective processing and power handling capabilities; whereas the feedback control is furnished using Lab-View. The performance of the proposed scheme is analyzed. The results confirm flexible control of the motor incorporated with the presented drive system which is supplied via solar power.